Does public funding have a halo effect? Evidence from Finnish SMEs - Lotta Väänänen (The Research Institute of the Finnish Economy (ETLA), 2003)
One commonly mentioned rationale for public funding is its positive signaling effect, often called the “halo-effect”, to the private sector financial institutions about the quality of the firm. This is based on the market failure argument based on the existence of asymmetric information between the financier and the firm, and lack of transparency, particularly in smaller firms. This paper empirically explores the effects of public funding on firms' willingness and ability to gain access to private sector financing. Overall, the results indicate that market failures based on asymmetric information exist, and that firms do take active steps in trying to make their firms more transparent and signal their quality to the financiers (e.g. by using internationally recognized auditors). This does seem have a positive effect on the firms' ability to raise external market finance. What kind of role public funding plays in reducing this asymmetry remains unclear. The crucial question that remains in interpreting the results in this paper is the order of moves: is it the public sector funding that induces further private sector financing, or is it the other way around? – – Julkisen rahoituksen saanti on usein sanottu antavan positiivisen signaalin yrityksen laadusta yksityisille rahoittajille, niin sanottu ”halo-efekti”. Tämä perustuu markkinapuute argumenttiin, johtuen varsinkin pienten yritysten heikosta läpinäkyvyydestä ja epäsymmetrisestä informaatiosta yritysten ja rahoittajien välillä. Tutkimme empiirisesti julkisen rahoituksen saannin vaikutuksia yritysten haluun ja mahdollisuuksiin saada rahoitusta yksityiseltä sektorilta. Tulokset viittaavat siihen, että epäsymmetriseen informaatioon perustuva markkinapuute on olemassa ja, että yritykset lisäävät läpinäkyvyyttään esimerkiksi käyttämällä kansainvälisesti tunnettuja tilintarkastajia. Tällä näyttää olevan positiivinen vaikutus mahdollisuuksiin saada rahoitusta yksityiseltä sektorilta. Julkisen rahoituksen rooli epäsymmetrisen informaation pienentämisessä jää tämän tutkimuksen valossa epäselväksi. Tärkeä kysymys johon tutkimus ei anna vastauksia on siirtojen järjestys: saako julkinen rahoitus aikaan lisärahoituksen saannin yksityiseltä sektorilta, vai onko se toisin päin?
Keywords: 330; Klein- und Mittelunternehmen; Wirkungsanalyse; Finnland; Wirtschaftsförderung